Orienting Electron Fillings in d Orbitals of Cobalt Single Atoms for Effective Zinc–Air Battery at a Subzero Temperature - Yan, Yan; Wen, Bihan; Liu, Mingkai; Lei, Hao; Yang, Jifeng; He, Siyuan; Qu, Zehua; Xia, Wei; Li, Hongliang; Zeng, Jie (Advanced Functional Materials, 2024)
Abstract The missions in extreme environments such as the moon, the Arctic/Antarctic, and the plateau require the operation of batteries at low temperatures even below the freezing point of water. Herein, it is reported that compressively stressed Co single atoms exhibit enhanced oxygen reduction reaction (ORR) activity and enable the effective operation of zinc–air battery at a subzero temperature. The compressive strain is generated by depositing Co single atoms on highly arced carbon layers with ultra‐small curvature radii ≈2 nm. The locally compressive strain on Co single atoms redistributes the electron fillings in d orbitals with different spatial orientations, thereby strengthening the adsorption of active intermediates and enhancing the activity toward ORR. As expected, compressively stressed Co single atoms outperform Co single atoms on a flat support without strain in terms of kinetic current density (31.09 mA cm −2 vs 0.35 mA cm −2 ) at 0.85 V during ORR. The integration of the catalyst into a Zn–air battery generates a superior power density of 54.8 mW cm −2 than the commercial Pt/C counterpart (24.1 mW cm −2 ) at −40 °C.